Double-valve infective endocarditis: clinical features and prognostic impact; a retrospective study in a surgical centre. (14th October 2021) - Scheggi, V; Vanni, F; Ceschia, N; Merilli, I; Sottili, E; Alterini, B; Stefano, P L; Marchionni, N
Abstract: Introduction: Most cases of infective endocarditis (IE) involve a single valve, and little is known concerning IE that simultaneously affects two valves. The involvement of more than one valve may imply more severe and extensive cardiac lesions. In these patients, surgery may be challenging. Purpose: We aimed to determine the clinical characteristics, the therapeutic strategy, and the prognostic impact of double-valve IE (DVIE). Method: We retrospectively included in the analysis 380 consecutive patients with definite active IE in a single surgical centre. The univariate and multivariate long-term survival was analysed by the Kaplan-Meier method and by stepwise Cox proportional hazards models, respectively. We repeated the mortality analysis using the propensity score matching technique, to adjust for baseline differences between SVIE and DVIE groups. Results: DVIE occurred in 60 of the total enrolled 380 patients (15.8%) and involved mostly the combination of mitral and aortic valves (N=52, 87%). Most patients had double-native IE (N=38, 63%). Staphylococci were significantly less frequent in patients with double-valve than single-valve IE (SVIE). The proportion of patients undergoing valve repair among those treated surgically was higher for patients with DVIE than for SVIE (p<0.001). Valve repair of at least one valve was associated with non-significant better survival than double replacement. DVIE was associated with higher all-cause mortality than SVIE (p<0.001). DVIE was not associated with a higher risk of relapse or non-fatal adverse events. Conclusions: DVIE represents a considerable proportion of overall cases of IE, mainly involving aortic and mitral valves, with a jet lesion on the mitral valve; Staphylococcus is significantly less frequent than in SVIE; DVIE is independently associated with higher mortality; finally, mitral valve repair is feasible in a considerable proportion of surgical cases. FUNDunding Acknowledgement: Type of funding sources: None.